1989
DOI: 10.2190/d73m-ta0m-rv6k-p5ak
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Suicidal Behavior in Long-Term Care Facilities: A Preliminary Report on an Ongoing Study

Abstract: The prevention of suicide and other forms of self-destructive behavior among elderly residents of institutions is a major consideration because of its importance from humanitarian, professional, and legal points of view. One major aim of this study is to determine the extent and nature of overt suicide, attempted suicide, and intentional life-threatening behavior (ILTB) in long-term care facilities and to identify differences in patterns of suicidal behavior by gender, age, and race. A random sample of 1080 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In a study of 463 LTC facilities housing 30,269 residents, Osgood et al . () estimated that the overall prevalence of suicidal behavior (i.e., suicidal thoughts, attempts, and completed suicide) among residents was 1%, with 80% of these cases involving indirect life‐threatening behavior as defined above (Osgood et al ., ). A follow‐up study showed that 19% of LTC facilities had at least one instance of suicidal behavior (Osgood and Brant, ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study of 463 LTC facilities housing 30,269 residents, Osgood et al . () estimated that the overall prevalence of suicidal behavior (i.e., suicidal thoughts, attempts, and completed suicide) among residents was 1%, with 80% of these cases involving indirect life‐threatening behavior as defined above (Osgood et al ., ). A follow‐up study showed that 19% of LTC facilities had at least one instance of suicidal behavior (Osgood and Brant, ).…”
Section: Resultsmentioning
confidence: 99%
“…The work of Osgood 6 , 7 and others 8 – 11 has helped define the extent of the problem of geriatric suicide and the need for additional empiric research. Yet, other than case reports, 6 , 11 , 12 only one psychological autopsy study that deals specifically with older persons has appeared in the psychiatric literature 13 .…”
mentioning
confidence: 99%
“…Their group nature has good fit for a population-based suicide prevention strategy. The involves reducing risk factors, enhancing protective factors and buffers to suicidality, and creating and sustain living environments promoting an optimal level of wellness for each resident (Podgorski et al, 2010). These can be parts of a suicide prevention program for a freestanding facility or a strategy implemented across a multi-facility chain.…”
Section: A Framework For Suicide Prevention In Snfsmentioning
confidence: 99%
“…A facility should review its existing policies, procedures, and programs from a suicide prevention perspective to determine if they may potentially mitigate or exacerbate risk. (Podgorski et al, 2010). Suicide risk exposure of residents is associated with facility variables such as auspice, staff turnover, and size (Osgood, 1992).…”
Section: A Framework For Suicide Prevention In Snfsmentioning
confidence: 99%